Assessment of Lung Cytological Atypia among Shisha Smokers. (2nd September 2012) - Yahia Babiker, Ali Yousif; Khair Abas, Isra Mohammed; Alzohairy, Mohammad A.; Ahmed, Hussain
Abstract : Objectives . The aim of this study was to assess frequency of lung epithelial atypia among Shisha users. Methods . Sputum samples were collected from 200 subjects (100 Shisha users (cases) and 100 nontobacco users (controls)). Cytological smears were prepared and demonstrated using Papanicolaou and silver nucleolar organizer region (AgNORs) methods. Results . Cytological atypia was identified among 2/100 (2%) of the cases, and no cytological atypia was found among controls. Respiratory squamous metaplasia was significantly higher among cases 42/100 (42%), compared to controls 7/100 (7%) (P < 0.001 ). Shisha users were found more susceptible for bacterial infections 34 (34%) compared to controls 3/100 (3%), (P < 0.0001 ). The mean AgNOR dots count was higher among cases (2.3 ± .23 ) than among controls (1 ± .2 ), P < 0.001 . Conclusion . In view of these findings, the consumption of Shisha is a risk factor for cellular proliferation activity in respiratory epithelium. The mean AgNORs count is a useful indicator for prediction of the risk of exposure to certain carcinogenic elements that may induce lung cancer.